21st Century Skills-Based Sociology Learning at SMA Muhammadiyah Kupang - Ondi Mantolas (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2024)
This research aims to determine the implementation of 21st-century skills-based sociology learning at Muhammadiyah High School Kupang. To determine the supporting and inhibiting factors for skills abad21-based sociology learning at Muhammadiyah High School. The benefits of this research are theoretical and practical. This research was conducted at SMA Muhammadiyah Kupang. This research uses a qualitative approach. The subjects in the research are sociology subjects, teachers, and classes. The research uses triangulation to see the validity of the data. The analysis used is data techniques, presenting data, and analyzing data. The results of 21st-century skills-based sociology learning are carried out by (1) the teacher conducting questions and answers and stimulating students to be motivated in questions and answers. (2) the teacher provides direction to students regarding the use of technology, and (3) the teacher motivates students to use cell phones. Supporting factors for 21st-century learning are (1) The teacher encourages students to connect ideals. (2) Teachers use LCD of Infocus during learning. The inhibiting factors for 21st-century learning are (1) Students use cell phones to play games and (2) cell phones have a bad influence on students. (3) Teachers are still rigid in implementing 21st-century learning. (4) Teachers are still not fluent in managing LCDs and laptop computers used in learning.